Fatal leptospirosis in southern sea otters from Central California: pathologic findings and detection of Leptospira interrogans - Margaret E. Martinez; Pádraig J. Duignan; Katherine C. Prager; Cara L. Field; Mary E. Gomes; Rinosh Mani; Lilian Carswell; Tim Tinker; Joseph Tomoleoni; Michael Murray; Ri K. Chang; James O. Lloyd-Smith; et al. (Frontiers in Marine Science, 2026)
Leptospira interrogans serovar Pomona infections cause periodic outbreaks in California sea lions (CSLs; Zalophus californianus ) and sporadic deaths in phocids. However, the frequency of infection and associated health impacts remain uncharacterized in sympatric threatened southern sea otters (SSOs; Enhydra lutris nereis ), which serve as important sentinels of coastal health. Given the broad impacts of L. interrogans on other marine mammals, our objective was to screen selected SSOs for infection, determine whether leptospirosis contributes to SSO mortality, and describe leptospiral-associated lesions. A retrospective review (2005–2025) identified 19 candidate cases that underwent detailed review, including Leptospira immunohistochemistry (IHC), serology, and polymerase chain reaction (PCR), with a special focus on renal and hepatic lesions. Kidney samples were PCR-positive for 74% (14/19) of suspected cases. For eight of these, DNA sequence-based serogroup typing detected L. interrogans serogroup Pomona. Seven of the 14 PCR-positive leptospirosis cases were classified as fatal based on positive renal IHC and moderate to severe tubulointerstitial nephritis. All fatal cases had anti- L. interrogans serovar Pomona antibody titers ≥1:25,600. The remaining seven PCR-positive cases were considered nonfatal leptospirosis due to minimal and/or unrelated renal lesions and negative IHC. Nonfatal Leptospira -infected cases ranged from seronegative to low positive (1:400) for serovar Pomona. Antibody titers for Leptospira PCR-negative cases were negative. In fatal cases, gross renal changes were often inapparent or characterized by miliary white cortical foci. Renal histologic lesions included tubulointerstitial nephritis, acute tubular necrosis, and suppurative tubulitis with intratubular bacteria, along with positive IHC staining for leptospiral antigen in the lesions. Gross hepatic changes were also inapparent in fatal cases, and histologic lesions were rare, characterized in one animal by hepatocellular dissociation and in two sea otters by limited leptospiral antigen detection by IHC. Most Leptospira -infected sea otters (71%, 10/14) stranded during higher rainfall months in California, suggesting possible land-to-sea transmission from terrestrial hosts. Given these findings, and because L. interrogans serovar Pomona infections have been confirmed in sympatric CSLs and terrestrial mammals from adjacent watersheds, a focused investigation of potential marine and terrestrial disease transmission dynamics could provide new information to reduce SSO mortalities.